2018
DOI: 10.3389/fimmu.2018.00475
|View full text |Cite
|
Sign up to set email alerts
|

The Acid–Base Balance and Gender in Inflammation: A Mini-Review

Abstract: In humans, acid-base balance is crucial to cell homeostasis. Acidosis is observed in numerous inflammatory processes, primarily acute conditions such as sepsis, trauma, or acute respiratory distress where females tend to exhibit better prognosis compared with males. The mechanisms underlying these gender-dependent differences are multiple, probably involving hormonal and genetic factors, particularly the X chromosome. Although pH influences multiple immunological functions, gender differences in acid-base bala… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
53
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(55 citation statements)
references
References 45 publications
1
53
1
Order By: Relevance
“…The production of pro- and anti-inflammatory cytokines was repeatedly shown to depend from the extracellular pH (for reviews, see Kellum et al, 2004b ; Okajima, 2013 ; Casimir et al, 2018 ). Although the different forms and severities of acidosis can differently influence cytokine production (Kellum et al, 2004b ), a proinflammatory effect, including enhanced TNF-α synthesis and augmented nuclear factor-κB activation, of hyperchloremic acidification was shown in activated macrophages by independent groups (Bellocq et al, 1998 ; Heming et al, 2001 ; Kellum et al, 2004a ).…”
Section: Discussionmentioning
confidence: 99%
“…The production of pro- and anti-inflammatory cytokines was repeatedly shown to depend from the extracellular pH (for reviews, see Kellum et al, 2004b ; Okajima, 2013 ; Casimir et al, 2018 ). Although the different forms and severities of acidosis can differently influence cytokine production (Kellum et al, 2004b ), a proinflammatory effect, including enhanced TNF-α synthesis and augmented nuclear factor-κB activation, of hyperchloremic acidification was shown in activated macrophages by independent groups (Bellocq et al, 1998 ; Heming et al, 2001 ; Kellum et al, 2004a ).…”
Section: Discussionmentioning
confidence: 99%
“…However, given the self-perpetuating cycle of oxidative stress and inflammation, it is not unexpected that a pro-inflammatory phenotype (increased TNFα and IL-17, decreased IL-10) is prevalent in IBS. Also, in the context of inflammation, a female bias has been reported, with females exhibiting higher inflammatory capacity and generally having poorer prognosis in chronic inflammatory disease [ 38 ].…”
Section: The Complexity That Is Ibsmentioning
confidence: 99%
“…The importance of considering inflammation in IBS, is underlined by several factors. Firstly, a recent review concluded that gender-differences in inflammation—specifically the fact that prognosis in chronic inflammatory conditions are worse in females, in line with the female predominance in IBS—cannot be fully accounted for by hormonal differences between genders [ 38 ]. Secondly, psychosocial stress is the most generally recognized risk factor for both development and relapse of IBS [ 222 ].…”
Section: Introductionmentioning
confidence: 99%
“…Similar observations were made by others in infectious diseases or septic shock, wherein males of any age showed worse prognosis [18]. Females have better prognosis, there is a hypotheses that it is probably ascribed to a higher neutrophilic in ammation and lower extracellular milieu's pH [19]. Considering the comorbidities and malignant diseases, we used Charlson score instead.…”
Section: Discussionmentioning
confidence: 64%